2021
DOI: 10.1128/mra.00898-21
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequences of Staphylococcus aureus Isolates from Positive Blood Cultures

Abstract: Staphylococcus aureus is a major cause of skin and soft tissue infections as well as bloodstream infections worldwide. Here, we report the draft genome sequences of 18 deidentified S. aureus clinical strains collected from positive blood cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To determine if clinical S. aureus isolates can grow in medium lacking arginine, 200 clinical isolates were selected and grown in both CDM-R and CDMG-R. One hundred isolates were collected from positive blood cultures (group 1), and an additional 100 isolates were collected from diverse sites, including skin and soft tissue, respiratory fluids, and bodily fluids (group 2). The BioProject accession number for these sequences is PRJNA731492 ( 35 ). Unexpectedly, the screen revealed that 54% and 53% of isolates from groups 1 and 2, respectively, demonstrated robust growth in CDM-R.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if clinical S. aureus isolates can grow in medium lacking arginine, 200 clinical isolates were selected and grown in both CDM-R and CDMG-R. One hundred isolates were collected from positive blood cultures (group 1), and an additional 100 isolates were collected from diverse sites, including skin and soft tissue, respiratory fluids, and bodily fluids (group 2). The BioProject accession number for these sequences is PRJNA731492 ( 35 ). Unexpectedly, the screen revealed that 54% and 53% of isolates from groups 1 and 2, respectively, demonstrated robust growth in CDM-R.…”
Section: Resultsmentioning
confidence: 99%